The dragon prophecy - Steer, Dugald (Dragonology chronicles, 2012)
When brother and sister dragonology students Daniel and Beatrice Cook join Dr. Drake in pursuing evil Alexandra Gorynitchka to the Lost Isle, where she is amassing an army of enslaved dragons to seek an ancient weapon that can kill hundreds of dragons at a single stroke, they learn of a Dragon Prophecy which may place a heavy burden on the siblings.